2017
DOI: 10.1080/1331677x.2017.1314823
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution, economic growth and health care expenditure

Abstract: In this article, we examine the role of environmental quality and economic growth in the determination of health expenditure in the Middle East and North Africa region (MENA) countries for the period 1995-2014 using Autoregressive Distributed Lag (ARDL) method to explore the estimating the impacts of economic growth and environmental quality on heath expenditure. The results show that health expenditure, income, CO 2 and PM 10 emissions are a cointegrated panel. While long-run elasticities show that income and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 17 publications
10
46
0
2
Order By: Relevance
“…Increased CO2 emissions will increase the burden of the health budget. These results were in accordance with the research conducted by [4,5] in which both studies tested the influence of revenues and CO2 on government spending on health sectors. In both studies, it found the result that CO2 gas emissions strongly affect government expenditure on the healthcare sector.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Increased CO2 emissions will increase the burden of the health budget. These results were in accordance with the research conducted by [4,5] in which both studies tested the influence of revenues and CO2 on government spending on health sectors. In both studies, it found the result that CO2 gas emissions strongly affect government expenditure on the healthcare sector.…”
Section: Resultssupporting
confidence: 92%
“…The research conducted by Abdullah [4] on the impact of environmental, economic and demographic factors on government spending on health sector in Malaysia shows the results where CO2, SO2, and NO2 gas emissions proved to be Have a significant influence on the government expenditure on the healthcare sector. The same results discovered by Khoshnevis [5] on their research on the influence of revenues, CO2, and PM10. In their research, they found the results that people's income and CO2 are the variables that most affect the Government's expenditure on the health sector.…”
Section: Introductionsupporting
confidence: 81%
“…They determined that CO 2 had a positive effect on healthcare expenditure and further analysis revealed that this impact was more powerful for states whose healthcare expenditures were higher. Khoshnevis Yazdi and Khanalizadeh [11] examined the contribution of environmental quality and economic growth in determining healthcare expenditures for countries located in the Middle East and North Africa for the timespan 1995-2014 by utilising the ARDL model. The findings revealed that increased economic growth elevated healthcare spending, meaning that economic growth is a significant indicator of health spending.…”
Section: Environment and Health Expendituresmentioning
confidence: 99%
“…The majority of previous researchers have concentrated on how to estimate the size of the income elasticity of healthcare, in addition to the policy implications in terms of the funding and distribution of healthcare resources. Recently conducted studies have also presented a link between health and environmental deterioration in order to examine empirical evidence [11][12][13]. The majority of previous studies have concentrated on the impact of CO 2 emissions on health spending.…”
Section: Introductionmentioning
confidence: 99%
“…Using a model examining the relationship between health expenditure, income, CO 2 emissions and PM 10 (particulate matter) emissions, for a panel of MENA (Middle East and North Africa) countries during 1995-2014, Khoshnevis Yazdi and Khanalizadeh [49] found an "overwhelming evidence between health expenditures and its determinants" [49] (p. 1189). Thus, economic growth in these countries will increase the consumption of fossil fuels, environmental degradation, and will lead to higher risk of pollution-induced health diseases and mortality.…”
Section: Health Expenditure Economic Growth and Air Pollutionmentioning
confidence: 99%